2023
DOI: 10.1017/s0031182023000446
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, phylogeny and intraspecific variability of Paradiplozoon species (Monogenea: Diplozoidae) parasitizing endemic cyprinoids in the Middle East

Abstract: Diplozoidae are common monogenean ectoparasites of cyprinoid fish, with the genus Paradiplozoon being the most diversified. Despite recent studies on Diplozoidae from Europe, Africa and Asia, the diversity, distribution and phylogeny of this parasite group appears to be still underestimated in the Middle East. The objective of this study was to investigate the diversity, endemism and host specificity of diplozoids parasitizing cyprinoid fish from the Middle East, considering this region as an important histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Diversity of fish ectoparasites in native Malagasy freshwater fish has been little studied in the past. The present study was a part of large parasitological investigation performed only in 4 localities of north-western Madagascar, however, documenting unknown diversity of fish parasites in isolated freshwater region with endemic fish fauna (i.e., Madagascar), the pattern which was previously shown for endemic freshwater fish in other regions i.e., Peri-Mediterranean and Middle East (Benovics et al ., 2017 , 2021 ; Rahmouni et al ., 2017 ; Řehulková et al , 2020 ; Nejat et al ., 2023 ). Prior to this study, 12 valid species of Dermoergasilus were known, including 1 species, specifically D. longiabdominalis , in mugilid hosts in Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity of fish ectoparasites in native Malagasy freshwater fish has been little studied in the past. The present study was a part of large parasitological investigation performed only in 4 localities of north-western Madagascar, however, documenting unknown diversity of fish parasites in isolated freshwater region with endemic fish fauna (i.e., Madagascar), the pattern which was previously shown for endemic freshwater fish in other regions i.e., Peri-Mediterranean and Middle East (Benovics et al ., 2017 , 2021 ; Rahmouni et al ., 2017 ; Řehulková et al , 2020 ; Nejat et al ., 2023 ). Prior to this study, 12 valid species of Dermoergasilus were known, including 1 species, specifically D. longiabdominalis , in mugilid hosts in Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…The preserved parasites were then sent to Shamsi's Parasitology Laboratory at Charles Sturt University, Australia, where the specimens underwent morphological examination and molecular analyses of their taxonomic classification and genetic characteristics. Parasites were morphologically examined as previously described by Gussev (1983) and Jalali et al (2005), and identified in accordance with previous publications (Galli et al 2010;Huang et al 2023;Nejat et al 2023). The terminology to describe various body-part structures is mainly in accordance with Galli et al (2010).…”
Section: Parasite Collection and Identificationmentioning
confidence: 93%
“…DNA was extracted using DNeasy Blood and Tissue kits (Qiagen, Hilden, Germany), as per the manufacturer's instructions, and modified (Shamsi et al 2018) the rDNA region was performed as previously described (Roohi et al 2019;Shamsi et al 2021;Nejat et al 2023).…”
Section: Parasite Collection and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradiplozoon (Diplozoidae) are relatively large-bodied monogenean parasites (with a body size ranging in different species from 0.8 to 8.2 mm) and common gill parasites on cyprinoid fish [ 7 ]. Among Paradiplozoon species, Paradiplozoon homoion is a generalist species with the highest range of host species [ 8 , 9 , 10 , 11 ]. Paradiplozoon homoion , like other diplozoid monogeneans, is representative of blood-feeding ectoparasites that degrade host blood components predominantly intracellularly [ 12 ].…”
Section: Introductionmentioning
confidence: 99%